Will there Be New Emerging-Market Economies in Africa b+L2280y the Year 2020? - Berthelemy, Jean-Claude.; Soderling, Ludvig (Washington, D.C. : International Monetary Fund, 2002)
This paper examines past African growth experience and attempts to simulate future ones. In addition to more commonly used determinants of total factor productivity, a measure of the effect of labor reallocation and an index of economic diversification are constructed and included as factors for long-term growth. A simple model is constructed for the purpose of simulating growth scenarios up to the year 2020 for Burkina Faso, Cote d'Ivoire, Ghana, Mali, Tanzania, and Uganda. Even if one makes relatively optimistic assumptions, Africa is not likely to reach "Asian tiger" levels of growth. The results also suggest that growth will depend, to a large extent, on educational investments and productivity gains in agriculture.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet